Exploring Teachers’ and Academic Researchers’ Opinion about Refugees’ Education and Physical Education - Papageorgiou Ελευθερία; Digelidis Νικόλαος; Syrmpas Ιωάννης; Papaioannou Αθανάσιος (Inquiries in Physical Education and Sport, 2018)
The following study examines and presents the points of view, the perceptions as well as the knowledge of physical education teachers and academic researchers, who interact and investigate the needs of refugees. The method of qualitative research has been implemented. More specifically, semi-structured interview across fifteen teachers and researchers (8 and 7 respectively) involved in the field of physical as well as intercultural education. The method of thematic analysis has been used to analyze the data gathered from the interviews. Based on the data analysis, the results demonstrate that both teachers and researchers consider physical education to be -thanks to the course’s nature- the most suitable course when it comes to facilitating the assimilation of foreign students. Both entities underline the need for teachers to be further trained, in order to properly deal with the intercultural school environment. Moreover, an effort has been made to describe the barriers which hinder the use of physical education as a means of facilitating intercultural education, an overview of the current state of the topic via the sample’s perspective has been examined and, finally, the hopes and expectations of physical education teachers and researchers concerning future improvement have been presented.